PERAN TARI GALOMBANG SEBAGAI LEGITIMASI STATUS BAGI MASYARAKAT PENGGUNADI NAGARI TANJUNG BALIK KECAMATAN X KOTO DIATAS KABUPATEN SOLOK - Eva Pauziah; Indrayuda (Universitas Negeri Padang, 2025)
This study discusses the role of the Galombang Dance as a symbol of legitimising social status among the community members in Nagari Tanjung Balik, District X Koto Diatas, Solok Regency. The Galombang Dance, as one of the traditional Minangkabau performing arts, has functions that go beyond mere entertainment. It plays an important role in the social structure of the community, particularly during customary events such as weddings and the welcoming of honoured guests, where the use of this dance often reflects the prestige, honour, and social position of the event organisers. This research employs a descriptive qualitative approach using ethnographic methods. Data was obtained through direct observation, in-depth interviews with artists and community leaders, as well as documentation of artistic activities at Sanggar Carano Pusako. Research findings indicate that the Galombang Dance has a strong symbolic meaning in reflecting social and cultural identity, especially for the upper middle class. This dance has also evolved in terms of its presentation, including movement variations, makeup, and costumes, while still maintaining the philosophical values passed down through generations. Thus, the existence of the Galombang Dance not only serves as a means of cultural preservation but also represents a way to reinforce status and identity within the social life of the people of Nagari Tanjung Balik.